2020
DOI: 10.1051/0004-6361/201937222
|View full text |Cite
|
Sign up to set email alerts
|

The CARMENES search for exoplanets around M dwarfs

Abstract: Context. For years, the standard procedure to measure radial velocities (RVs) of spectral observations consisted in cross-correlating the spectra with a binary mask, that is, a simple stellar template that contains information on the position and strength of stellar absorption lines. The cross-correlation function (CCF) profiles also provide several indicators of stellar activity. Aims. We present a methodology to first build weighted binary masks and, second, to compute the CCF of spectral observations with t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 59 publications
4
76
0
Order By: Relevance
“…Indeed, due to blended lines that are in some way unique for each star depending on the stellar temperature, metallicity, v sin(i) or instrumental resolution, a generic mask will in some case produce spurious RV signals, which was demonstrated in Cretignier et al (2020a). We note that similarly to Dumusque (2018) and Cretignier et al (2020a), Lafarga et al (2020) showed that tailored lines selections, produced by their public code RACCOON, can be useful to boost the S/N and decrease the photon noise, which produces in general better RV precision.…”
Section: Stellar Mask Optimisation and Lbl Rvsmentioning
confidence: 63%
“…Indeed, due to blended lines that are in some way unique for each star depending on the stellar temperature, metallicity, v sin(i) or instrumental resolution, a generic mask will in some case produce spurious RV signals, which was demonstrated in Cretignier et al (2020a). We note that similarly to Dumusque (2018) and Cretignier et al (2020a), Lafarga et al (2020) showed that tailored lines selections, produced by their public code RACCOON, can be useful to boost the S/N and decrease the photon noise, which produces in general better RV precision.…”
Section: Stellar Mask Optimisation and Lbl Rvsmentioning
confidence: 63%
“…The SIMBAD query provides line-of-sight velocities for 287 objects. Among them, 129 come from Gaia DR2 or its catalogue of radial velocity standard stars (Soubiran et al 2018), and 48 precise measurements come from Lafarga et al (2020). Radial velocities of multiple systems may be inaccurate, but we tried to use the same source for the two components of a binary system Notes.…”
Section: Line-of-sight Velocitiesmentioning
confidence: 99%
“…All redetermined parameters (T eff , L , R , and M ) match the values published by Gaidos et al (2014) and Gaia Collaboration (2018) within 1σ. Furthermore, we used the precise astrometric data of Gaia DR2, the absolute RV measured on the stacked CARMENES spectra as in Lafarga et al (2020), and the prescription of Johnson & Soderblom (1987) for measuring the Galactocentric space velocities UVW. Using this kinematic information with the BANYAN Σ tool (Gagné et al 2018), we classified TOI-1235 as a field star in the Galactic thin disk not associated with any young stellar kinematic group.…”
Section: Stellar Propertiesmentioning
confidence: 99%